DNA Polymerase λ Inactivation by Oxidized Abasic Sites() - Stevens, Adam J. (2013)
Base excision repair plays a vital role in maintaining genomic integrity in mammalian cells. DNA polymerase λ is believed to play a backup role to DNA polymerase β in base excision repair. Two oxidized abasic lesions that are produced by a variety of DNA damaging agents, including several antitumor antibiotics, the C4′-oxidized abasic site following Ape1 incision (pC4-AP) and 5′-(2-phosphoryl-1,4-dioxobutane) (DOB), irreversibly inactivate Pol β and Pol λ. The interactions of DOB and pC4-AP with Pol λ are examined in detail using DNA substrates containing these lesions at defined sites. Single turnover kinetic experiments show that Pol λ excises DOB almost 13-times more slowly than a 5′-phosphorylated 2-deoxyribose (dRP). pC4-AP is excised approximately twice as fast as DOB. The absolute rate constants are considerably slower than those reported for Pol β at the respective reactions, suggesting that Pol λ may be an inefficient backup in BER. DOB inactivates Pol λ approximately 3-fold less efficiently than it does Pol β and the difference is attributable to a higher K(I) (33 ± 7 nM). Inactivation of Pol λ’s lyase activity by DOB also prevents the enzyme from carrying out polymerization following preincubation of the protein and DNA. Mass spectral analysis of GluC digested Pol λ inactivated by DOB shows that Lys324 is modified. There is inferential support that Lys312 may also be modified. Both residues are within the Pol λ lyase active site. Protein modification involves reaction with released but-2-ene-1,4-dial. When acting on pC4-AP, Pol λ achieves approximately 4 turnovers on average before being inactivated. Lyase inactivation by pC4-AP is also accompanied by loss of polymerase activity and mass spectrometry indicates that Lys312 and Lys324 are modified by the lesion. The ability of DOB and pC4-AP to inactivate Pol λ provides additional evidence that these lesions are significant sources of the cytotoxicity of DNA damaging agents that produce them.